Individual and contextual vulnerability factors involved in the human trafficking process of minors and adults serviced by Hope Risen : a case study - van der Westhuizen, Amanda (University of Pretoria, 2022)
Mini-Dissertation (MA (Counselling Psychology))--University of Pretoria, 2022.